HUBUNGAN DUKUNGAN SOSIAL KELUARGA DENGAN TINGKAT KECEMASAN IBU PRIMIGRAVIDA TRIMESTER III DALAM MENGHADAPI PROSES PERSALINAN DI WILAYAH KERJA PUSKESMAS KOTA MATSUM MEDAN - hendry kiswanto mendrofa (STIKes Murni Teguh, 2019)
Mothers who are undergoing pregnancy experience changes physically, psychologically and mentally therefore pregnant women are required not only to be physically ready, but also thirsty to be mentally prepared. Mental changes in the mother will affect the emotions of the mother. In the third trimester the psychological changes that occur include feeling anxiety and anxiety about the birth of her baby, feelings of fear of death, birth trauma and fear of birth defects. If the emotional influence of the mother is not supported by a harmonious family environment or conducive living environment, then this can cause emotional and physical disturbance (mild to severe). Preventing this from happening, then family social support for pregnant women is very important so that mothers can undergo pregnancy until the delivery process well. This type of research uses a correlation research design with the Spearman correlation test. The number of samples in the study were 30 respondents with a sampling technique that is purposive sampling. This research instrument consisted of 2 questionnaires namely a family social support questionnaire (Likert scale) and an anxiety level questionnaire (Hamilton rating scale for anxiety). The results showed that there was a relationship of family social support with anxiety levels of trimester III primigravida mothers in the face of labor, the Spearman correlation test results obtained r value of 0.751 categorized as